The Rabbi's Wife : the Rebbetzin in American Jewish Life. - Schwartz, Shuly Rubin (NYU Press, 2006)
2006 National Jewish Book Award, Modern Jewish Thought. Long the object of curiosity, admiration, and gossip, rabbis' wives have rarely been viewed seriously as American Jewish religious and communal leaders. We know a great deal about the important role played by rabbis in building American Jewish life in this country, but not much about the role that their wives played. The Rabbi's Wife redresses that imbalance by highlighting the unique contributions of rebbetzins to the development of American Jewry. Tracing the careers of rebbetzins from the beginning of the twentieth century until the pr.